Evaluación de las alteraciones cognitivas en adultos mayores - Delgado D., Carolina; Salinas C., Pablo (Revista Hospital Clínico Universidad de Chile, 2009)
Dementia is characterized by at least two cognitive domains defects that affect daily living activities. Before it, cognitive impairment is mild (Mild Cognitive Impairment). In next years, dementia will become a public health matter, so it is very important to have proper tools that allow early diagnosis. These tools should be validated, sensitive, specific and easy to perform by non specialist physician. We discuss utility and weakness of a selected group of behavior and cognitive scales.